Re-evaluation of Underflow Energy Dissipation Effect Based on AHP-fuzzy Comprehensive Evaluation Method - LIU Jialin; QIU Yong; ZHOU Xinyu; PU Jinbing; JIANG Yujia (Renmin Zhujiang)
The effects of current underflow energy dissipation are basically evaluated by a single indicator (energy dissipation rate) based on engineering safety.To better adapt to the construction needs of ecological water conservancy,this paper comprehensively analyzes all relevant factors of underflow energy dissipation and conducts the qualitative and quantitative analysis of multiple indicators by the application of hierarchical analysis and fuzzy comprehensive evaluation.It sets two criterion layers of main characteristic indicators (energy loss,aeration concentration of water body after energy dissipation,fluctuation pressure,and tail water flow pattern) and minor characteristic indexes (anti-impact flow velocity of downstream,Froude number of pre-jump section, and inundation degree).Then,it calculates the corresponding weights and degree of membership respectively to obtain the re-evaluation result of the energy dissipation effect of a grid underflow energy dissipater being 83.3 points (B grade).The results show that the comprehensive evaluation based on multiple factors can better take into account the ecological requirements and other influencing factors of the downstream river on the premise of meeting engineering safety.